A crystalline dihydroxyanthraquinone anodic material for proton batteries. (December 2021) - Yu, Juezhi; Li, Jing; Leong, Zhi Yi; Li, Dong-sheng; Lu, Jiong; Wang, Qing; Yang, Hui Ying
Abstract: As a class of redox-active compounds, anthraquinones (AQs) have been investigated in rechargeable metallic ion batteries. In this work, it is found that protons (H + ) can be reversibly intercalated and deintercalated in crystalline 2, 6-dihydroxyanthraquinone (DHAQ) at a potential of −0.21 V vs. Ag/AgCl in acidic solution and exhibits a specific capacity of 110 mAh g −1 . This unique property is leveraged in a rechargeable proton battery system with a DHAQ anode and an Mn 2+ cathode. During battery cycling, a morphology evolution from particulate DHAQ into centimeter-scale nanofibers is observed. It is revealed that the evolution of morphology stems from a realignment of the DHAQ molecule. The quinone proton battery delivers an equilibrium voltage of 1.1 V, and the capacity retention rate could be as high as 100% after 2600 cycles. This study showcases a unique proton (de)intercalation chemistry in crystalline AQ and demonstrates the viability of the organic proton battery system. Graphical abstract: Image 1 Highlights: The redox center of a quinone molecule is an aromatic ring instead of the typical –(C=O)– group. The redox mechanism of 2, 6-dihydroxyanthraquinone (DHAQ) is a H + (de)intercalation process. The diffusion coefficient ( D 0 ) of H + in DHAQ was determined to be fast reaction kinetics. high performance proton battery system was developed at room temperature.